1998
DOI: 10.1177/096032719801700402
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the protocol of OECD guideline 407 (28-day repeated dose oral toxicity test in the rat) to detect potential immunotoxicity of chemicals

Abstract: To indicate the immunotoxic potential of chemicals the examinations prescribed by OECD Guideline 407 were extended by the following additional toxicological, haematological, histopathological, and immune function examinations: absolute and relative organ weight of spleen, thymus, popliteal lymph nodes, lung and brain; histopathology of thymus, mesenteric lymph nodes, popliteal lymph nodes, bone marrow (femur), Peyer's patches (ileum), lungs and colon; PFC assay (spleen), T cell proliferation and NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The assessment of direct immunotoxicity is an important part of the overall toxicological investigation of chemicals (Lankveld et al, 2010). Other authorities such as the Organisation for Economic Cooperation and Development (OECD) (Institoris et al, 1998) and the Environmental Protection Agency (EPA, 2013) stress the need for safety assessment of food contaminants and environmental pollutants. Other authorities such as the Organisation for Economic Cooperation and Development (OECD) (Institoris et al, 1998) and the Environmental Protection Agency (EPA, 2013) stress the need for safety assessment of food contaminants and environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of direct immunotoxicity is an important part of the overall toxicological investigation of chemicals (Lankveld et al, 2010). Other authorities such as the Organisation for Economic Cooperation and Development (OECD) (Institoris et al, 1998) and the Environmental Protection Agency (EPA, 2013) stress the need for safety assessment of food contaminants and environmental pollutants. Other authorities such as the Organisation for Economic Cooperation and Development (OECD) (Institoris et al, 1998) and the Environmental Protection Agency (EPA, 2013) stress the need for safety assessment of food contaminants and environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…For environmental chemicals, no dedicated OeCD test guidelines exist, but extensions were made to 28-day repeat dose toxicity testing (tG 407) (Institóris et al, 1998 • Changes in total and differential white blood cell counts, i.e., leukocytopenia/leukocytosis, granulocytopenia/granulocytosis, or lymphopenia/ lymphocytosis;…”
Section: Consideration 3: Determining Immunosuppression In Vivo and Imentioning
confidence: 99%
“…Advisory dose levels for Wistar rats as the result of immunotoxicity studies are 5 to 25 mg per kg of body weight per day, the maximal tolerated dose for rats is approximately 15 to 25 mg per kg body weight per day, and the duration of oral treatment to investigate toxicological effects in rats is 28 days according to OECD-rules (OECD: Organization for Economic Cooperation and Development). 11,13 Whereas AZA toxicity in rats is well described, there is little experience with AZA metabolite concentration levels close to maximum tolerated AZA doses. 6-TG and 6-MMP concentrations, as analyzed at the end of the treatment period in our study, showed a wide range even within groups receiving equal AZA dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms in AZA_s action on inflammatory conditions are not understood in detail, but it has been shown that AZA affects macrophage cytotoxicity, lymphocyte proliferation, and natural killer cell activity. [11][12][13] The inflammatory response of these cells seems to contribute to the healing process of intestinal anastomoses, because they release a number of cytokines and growth factors, and in this Vol. 50, No.…”
Section: Discussionmentioning
confidence: 99%